Application of Inlislite Version 3.0 at Library and Archives Service of Bengkulu Province - Imam Apriansah; Nurhayati Darubekti; Lailatus Sa’diyah (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2022)
Background of the study: An application is a pair or installation of technology in a library in the form of a service transition, where the transition is moving the library to realize service renewal and the use of technology into their daily activities in order to increase to usability of a library. This study aims to determine how the application INLISLite version 3.0 at the library and archives service of Bengkulu province in improving its services for users who need the information. Purpose: This study aims to find out how the application of INLISLite version 3.0 at the Bengkulu Province Library and Archives Service uses the TAM (Technology Accepted Model) theory from Davis. Method: The design of this research is descriptive qualitative. The research was conducted by in-depth interviews with three informants from the circulation service section. Researchers use the theory of TAM (Technology Accepted Model) from Davis, focusing on perceptions of convenience and usefulness Findings: The results of the study show that the application of INLISLite version 3.0 at the Bengkulu Provincial Library and Archives Service has been carried out well, very easy and useful in helping the work of the circulation librarian. Conclusion: The application of the INLISLite application version 3.0 at the Bengkulu Provincial Library and Archives Service is very easy and useful in helping the work of librarians who are reviewed through the TAM model with two indicators of convenience and usability, each of which has 6 important aspects, namely easy to learn, controllable, and easy to use. understandable, flexible, easy to skill, easy to use, speed up work, improve performance, increase productivity, effectiveness, simplify work and be useful.